Pengaruh Model Teaching Games for Understanding Terhadap Peningkatan Kemampuan Pukulan Servis Pendek Dalam Pembelajaran Bulutangkis - Setiawan, Hari; Mury Syafei, Muhamad; Suherman, Asep (Jurnal Porkes, 2024)
The purpose of this study was to examine how much influence the teaching games for understanding model has on improving the ability to hit short serves in badminton learning. This study uses a quantitative approach with experimental research methods. The population of this study was class VIII SMPN 6 West Karawang totaling 400 students. The sample used in this study was simple random sampling, using the slovin formula totaling 40 students. The form of research design is pre-experimental design with the form of one group pretest postest design. The research instrument used a french short serve test instrument. The results of this study are the average before treatment and after treatment has increased significantly, namely the mean pretest 12.2000 to the mean posttest 21.5500. Meanwhile, the results of the calculation of the paired sample T test hypothesis testing are a significance value (2-tailed) of 0.000 <0.05, meaning that there is a significant influence between the average value before treatment and the average value after treatment. It can be concluded that the teaching games for understanding model has an effect on improving the ability of badminton short serve shots of class VIII students of SMPN 6 West Karawang.